Analisis Pembelajaran Kooperatif Model Team Games Tournament Pada Mata Pelajaran Pendidikan Pancasila - M Aqim Nur Hubi; Febrian Alwan Bahrudin; Euis Sundarti; Sinta Nuryuliani; Indah Cahaya Mulia; Noviyasti Alfanda; Cicih Cicih (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The research was conducted against the backdrop of students' difficulty understanding the subject matter and their lack of enthusiasm for teaching and learning activities, which affected their learning results when they participated in class. This study uses the Team Games Tournament (TGT) model in Pancasila Education courses with mutual cooperation materials to investigate whether or not there are changes in learning outcomes and student performance. Descriptive analytical research methodology using a qualitative approach is employed. This study's findings showed a 13.5% rise. The average score was 77.5% before receiving the Team Games Tournament (TGT) therapy; following the Team Games Tournament (TGT) treatment, the average score increased to 91%.  In session 1 the number of students who met the good criteria was 68%, while in session 2 it was 100%.